Endoscopic assisted insetting of free flaps in anterior skull base reconstruction: A preliminary report of five cases. Issue 4 (3rd December 2019) - Rodriguez‐Lorenzo, Andres; Driessen, Caroline; Mani, Maria; Lidian, Adnan; Gudjonsson, Olafur; Stigare, Erik
Abstract: Introduction: Free vascularized tissue may provide a robust reconstruction after anterior skull base surgery. We report our technique and outcomes of the endoscopic inset of free flaps in anterior skull base reconstructions. Methods: Between 2016 and 2018, endoscopic tumor removal and reconstruction of anterior skull base pathology was performed in five patients aged 20–72 years old (four male, one female). The tumors included three neuroblastomas, a carcinoma, an adenoma, and a melanoma. The median size of the defect was 3.7 × 6.6 cm. Transmaxillary access was gained through the upper sulcus and an anterior and medial maxillectomy. The flap inset was facilitated by the endoscope. The donor vessels were tunneled through the sinus and through the cheek to the facial vessels without the use of the endoscope. Results: In three cases a vastus lateralis flap was used, in one case an adipofascial ALT flap and in one case an adipofascial radial forearm flap. Separation of intracranial and sinonasal spaces was confirmed by radiological and endoscopic examinations. There was no flap failure and one case with partial necrosis. One of the flaps needed to be trimmed as it obliterated the nasal cavity and in one of the cases the flap was repositioned postoperatively. Two cases had infectious complications. The mean follow‐up of the patients was 13.8 months. Conclusions: Endoscopic assisted inset of a free flap in the anterior skull base was feasible in the five cases we present. A dedicated, multidisciplinary approach is mandatory for surgical innovation like this.